The Role of Microglia in Perioperative Neuroinflammation and Neurocognitive Disorders - Saxena, Sarah; Kruys, Veronique; Vamecq, Joseph; Maze, Mervyn (Frontiers in Aging Neuroscience, 2021)
The aseptic trauma of peripheral surgery activates a systemic inflammatory response that results in neuro-inflammation; the microglia, the resident immunocompetent cells in the brain, are a key element of the neuroinflammatory response. In most settings microglia perform a surveillance role in the brain detecting and responding to “invaders” to maintain homeostasis. However, microglia have also been implicated in producing harm possibly by changing its phenotype from its beneficial, anti-inflammatory state (termed M2) into an injurious pro-inflammatory state (termed M1); it is likely that there are intermediates states between these polar phenotypes and some consider that a gradient exists with a number of intermediates, rather than a strict dichotomy between M1 and M2. In the pro-inflammatory phenotypes, microglia can disrupt synaptic plasticity such as long- term potentiation that can result in disorders of learning and memory of the type observed in Peri-operative Neurocognitive Disorders. Therefore, investigators have sought strategies to prevent microglia from provoking this adverse event in the perioperative period. In preclinical studies microglia can be depleted by removing trophic factors required for its maintenance; subsequent repopulation with a more beneficial microglial phenotype may result in memory enhancement, improved sensory motor function, as well as suppression of neuroinflammatory and oxidative stress pathways. Another approach consists of preventing microglial activation using the non-specific P38 MAP kinase blockers such as minocycline. Perhaps a more physiologic approach is the use of inhibitors of potassium (K) channels that are required to convert the microglia into an active state. In this context the specific K channels that are implicated are termed Kv1.3 and KCa3.1 and high selective inhibitors for each have been developed. Data are accumulating demonstrating the utility of these K channel blockers in preventing Perioperative Neurocognitive Disorders.